Effectiveness of Artificial Intelligence Models for Cardiovascular Disease Prediction: Network Meta-Analysis - Baashar Y.; Alkawsi G.; Alhussian H.; Capretz L.F.; Alwadain A.; Alkahtani A.A.; Almomani M. (Hindawi Limited, 2023)
Decision trees; Deep learning; Diagnosis; Diseases; Forecasting; Heart; Neural networks; Random processes; Support vector machines; Cardiovascular disease; Causes of death; Confidence interval; Electronic database; Heart failure; Intelligence models; Learning models; Meta-analysis; Odd ratios; Web of Science; Cardiology; artificial intelligence; Bayes theorem; cardiovascular disease; female; human; machine learning; male; meta analysis; network meta-analysis; Artificial Intelligence; Bayes Theorem; Cardiovascular Diseases; Female; Humans; Machine Learning; Male; Network Meta-Analysis